ENERGY AND CLEAN WATER POTENTIAL IN A CLOSED SYSTEM SUGAR FACTORY - Gunawan, Gunawan (ITScience (Information Technology and Science), 2023)
The production and demand for sugar in Indonesia increases every year. This condition has the potential to make the sugar factory a model of a closed system sugar factory, because the increase in white crystal sugar (GKP) production will increase the by-products (bagasse, filter cake, molasses and wáter). The closed system sugar factory is a GKP factory integrated with the power generation and clean water treatment industries. In this model, the raw material for sugar cane is not only used as sugar but also as a source of renewable energy and clean water. The purpose of this study was to analyze the potential utilization of by-products in the form of bagasse, filter cake, molasses and water in white crystal sugar factories. The research method is mass balance using input, process and output data at the sugar factory and secondary data. The results of this study have provided information about the potential for energy and water in closed system sugar production. The energy potential for power generation from blotong is 1 730.2 MJ/ton GKP, molasses is 5 939.0 MJ/ton GKP. The energy consumption at the power plant from blotong is 56.1 MJ/ton GKP, molasses is 408 MJ/ton GKP. The potential for clean water from water treatment for 1 ton of GKP is 4.6 tons, equivalent to 0.4 tons of clean water per ton of sugarcane.